Preparation method and application of solvent-free special heavy anti-corrosion material
By adding specific additives and modified fillers to solvent-free epoxy resin coatings, special solvent-free heavy anticorrosion materials are prepared, which solves the problem of insufficient performance of existing coatings in harsh environments and achieves high-performance heavy anticorrosion effects.
Patent Information
- Application Number
- CN202411707039.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing solvent-free epoxy resin coatings are difficult to meet the standards of heavy anticorrosion coatings in harsh corrosion environments, with low oxygen index and poor flame retardant performance.
Using bisphenol epoxy resin as the matrix, a special heavy anticorrosion material without solvent was prepared by adding diluents, leveling agents, organic modifiers, defoaming agents, inorganic fillers and curing agents. Among them, the nano-titanium powder and graphene oxide composite filler have been modified to improve the heat resistance, wear resistance and corrosion resistance of the material.
The heavily anticorrosive materials produced have excellent heat resistance, wear resistance and corrosion resistance, significantly improved flame retardant performance, less VOC volatilization, and are environmentally friendly. They are suitable for harsh corrosion environments such as desulfurization towers, gas pipelines and gas cabinets.
Smart Images

Figure BDA0005154751660000031 
Figure BDA0005154751660000041 
Figure BDA0005154751660000042
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coatings, and in particular, relates to a preparation method and application of a solvent-free special heavy-duty anti-corrosion material. Background Art
[0002] As global environmental issues become more and more prominent, the concept of "environmental protection, energy saving, and health" is becoming more and more popular. As an important industry in the chemical industry, coatings are facing severe challenges in environmental protection. Therefore, the development of environmentally friendly coatings has broad market prospects.
[0003] Environmentally friendly coatings include water-based coatings, high-solid coatings, powder coatings, solvent-free coatings and radiation-cured coatings. Among them, solvent-free coatings do not add organic solvents during the coating preparation process or during the coating use process, so they can effectively control the emission of volatile organic compounds (VOCs) and are environmentally friendly. The most widely used solvent-free coating is solvent-free epoxy resin coating. Epoxy resin has excellent anti-corrosion performance, good adhesion to metal and non-metal composite materials, excellent chemical resistance and safety performance, high hardness, good flexibility and other advantages, and is widely used in the field of anti-corrosion coatings.
[0004] Anticorrosive coatings are generally divided into conventional anticorrosive coatings and heavy-duty anticorrosive coatings. Conventional anticorrosive coatings are used to prevent corrosion of metals and other materials under normal conditions, protecting the service life of non-ferrous metals. Heavy-duty anticorrosive coatings are anticorrosive coatings that can be used in harsh corrosive environments such as desulfurization towers, gas pipelines, and gas tanks, relative to conventional anticorrosive coatings. They have a longer protection period than conventional anticorrosive coatings. However, general solvent-free epoxy resin coatings are still difficult to meet the requirements for use in harsh environments and do not meet the standards of heavy-duty anticorrosive coatings. In addition, epoxy resins have a low oxygen index and poor flame retardant properties. In summary, there is an urgent need to invent a solvent-free special heavy-duty anticorrosive material that can solve the above problems, so as to meet the application of solvent-free epoxy resin coatings in harsh corrosive environments such as desulfurization towers, gas pipelines, and gas tanks. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a preparation method and application of a solvent-free special heavy-duty anti-corrosion material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a solvent-free special heavy-duty anticorrosive material comprises the following steps:
[0008] Add bisphenol A epoxy resin and diluent into a mixer and stir for 15-30 minutes, then add leveling agent, organic modifier and defoamer in sequence and stir for 15-30 minutes, then add inorganic filler and stir for 15-30 minutes, finally mix with curing agent and stir evenly to obtain solvent-free special heavy-duty anti-corrosion material.
[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of bisphenol A epoxy resin, 10-20 parts of diluent, 1-2 parts of leveling agent, 5-15 parts of organic modifier, 1-2 parts of defoamer, 24-36 parts of inorganic filler, and 15-25 parts of curing agent.
[0010] Furthermore, the diluent is one of n-butyl glycidyl ether, allyl glycidyl ether and phenyl glycidyl ether.
[0011] Furthermore, the curing agent is one of triethylamine, triethanolamine and o-hydroxybenzyldimethylamine.
[0012] The bisphenol epoxy resin as the matrix gives the material excellent corrosion resistance; the curing agent is a tertiary amine curing agent, which can effectively promote the curing of the epoxy resin.
[0013] Furthermore, the inorganic filler is prepared by the following steps:
[0014] After adding nano titanium powder, graphene oxide and ethanol aqueous solution into a flask, the mixture is placed in a magnetic stirrer for magnetic stirring for 30-60 minutes, and then ultrasonically treated for 30-60 minutes to evenly disperse the nano titanium powder and graphene oxide, and silane coupling agent KH-550 is added, the reaction temperature is controlled at 60°C, and the reaction is carried out for 6 hours. Stirring is continued during the reaction. After the reaction is completed, reduced pressure distillation, washing, and freeze-drying are performed to obtain an inorganic filler.
[0015] Furthermore, the usage ratio of nano titanium powder, graphene oxide, ethanol aqueous solution, and silane coupling agent KH-550 is 1 g: 1 g: 100 mL: 4.3 g.
[0016] The prepared inorganic filler is a composite filler of nano-titanium powder and graphene oxide, and the filler is modified by using a silane coupling agent KH-550, that is, an organic layer is formed on its surface, which can improve the surface hydrophobicity of the filler, improve the compatibility of the inorganic filler with the epoxy resin matrix, promote the dispersion of the inorganic filler, give full play to the performance of the inorganic filler, and greatly enhance the heat resistance, wear resistance and corrosion resistance of the material.
[0017] Further, the organic modifier is prepared by the following steps:
[0018] S1. In a three-necked flask equipped with a stirring device, tris(hydroxymethyl)aminomethane hydrochloride, triethylamine and N,N-dimethylformamide (DMF) were mixed at room temperature, placed in an ice-water bath at 5°C, and stirred for 35 minutes. Then, phosphorus oxychloride was slowly added dropwise, and the temperature was controlled not to exceed 20°C during the addition. After the addition was completed, the temperature was raised to 80°C and kept for reaction for 8 hours. After the reaction was completed, the solvent was removed by filtration under reduced pressure, and the filter cake was washed 3-4 times with anhydrous ethanol, vacuum dried, and ground to obtain intermediate 1; the ratio of tris(hydroxymethyl)aminomethane hydrochloride, triethylamine, N,N-dimethylformamide, and phosphorus oxychloride was 16.3g:15mL:100mL:15.3g;
[0019] Tris(hydroxymethyl)aminomethane hydrochloride reacts with phosphorus oxychloride to obtain intermediate 1; the specific reaction process is as follows:
[0020]
[0021] S2. In a three-necked flask equipped with a stirring device, the intermediate 1, hexafluoroglutaryl chloride and N,N-dimethylformamide were mixed and stirred continuously for 5 minutes, and then dicyclohexylcarbodiimide (DCC) was added, and the mixture was kept in a water bath at 55°C for 4 hours. After the reaction was completed, the mixture was filtered, rotary evaporated, and the solvent was removed by vacuum distillation to obtain the intermediate 2; the ratio of the intermediate 1, hexafluoroglutaryl chloride, N,N-dimethylformamide, and dicyclohexylcarbodiimide was 16.5 g: 28.4 g: 150 mL: 20.6 g;
[0022] Under the catalysis of DCC, intermediate 1 and hexafluoroglutaryl chloride undergo amidation reaction, and intermediate 2 is obtained by controlling the molar ratio of the two to be close to 1:1 and the hexafluoroglutaryl chloride to be slightly excessive; the specific reaction process is as follows:
[0023]
[0024] S3. In a three-necked flask equipped with a stirring device, the intermediate 2, 4,4'-diaminodiphenyl sulfone and N,N-dimethylformamide were mixed and stirred evenly, and then dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 8 hours. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 3. The ratio of the amount of intermediate 2, 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide and dicyclohexylcarbodiimide was 40.4 g:25.6 g:200 mL:20.6 g.
[0025] Under the catalysis of dicyclohexylcarbodiimide, intermediate 2 and 4,4'-diaminodiphenyl sulfone undergo amidation reaction, and intermediate 3 is obtained by controlling the molar ratio of the two to be close to 1:1 and a slight excess of 4,4'-diaminodiphenyl sulfone; the specific reaction process is as follows:
[0026]
[0027] S4. In a three-necked flask equipped with a stirring device, p-phenylene diisocyanate, intermediate 3 and N,N-dimethylformamide were mixed, tributyltin (catalyst) was added and mixed and stirred evenly, the temperature was gradually increased to 70°C, and the reaction was kept warm for 6 hours. Stirring was continued during the reaction. After the reaction was completed, the solvent was removed by vacuum distillation, washed with toluene 2-3 times, and vacuum dried to obtain an organic modifier; the ratio of p-phenylene diisocyanate, intermediate 3, N,N-dimethylformamide and tributyltin was 18.3g:61.7g:200mL:0.2g;
[0028] The isocyanate group in p-phenylene diisocyanate reacts with the amino group on the intermediate 3 to generate a urea group. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of p-phenylene diisocyanate, only one isocyanate group on p-phenylene diisocyanate participates in the reaction to obtain an organic modifier. The specific reaction process is as follows:
[0029]
[0030] The prepared organic modifier molecule contains CF bond, diphenyl sulfone, caged phosphonate and isocyanate structure, wherein the CF bond has small polarity and strong bond energy. The higher the chemical bond energy, the better the stability. It not only improves the heat resistance of the epoxy resin matrix, but also the CF bond can well coat the CC main chain to improve the corrosion resistance of the matrix. The introduced diphenyl sulfone can not only enhance the heat resistance of the matrix, but also desulfurize to generate SO2, sulfurous acid and water under heat, which can promote the Fries rearrangement reaction of the matrix, accelerate the carbonization of the matrix, and effectively enhance the flame retardant performance of the matrix. In addition, the introduced caged phosphonate structure is A green and environmentally friendly flame retardant with strong stability. It can promote the formation of a carbon layer and inhibit the release of smoke when burning. It can play a synergistic role with diphenyl sulfone in the organic modifier molecule to greatly improve the flame retardant properties of the matrix. Finally, the isocyanate group in the organic modifier molecule can react with the epoxy group in the epoxy resin matrix to generate a five-membered ring oxazolidone structure, which can further improve the heat resistance and a certain degree of mechanical properties of the epoxy resin matrix. Moreover, the organic modifier is connected to the epoxy resin matrix through chemical bonds, which improves the migration and exudation resistance of the small molecules of the organic modifier and improves the stability of the organic modifier.
[0031] Beneficial effects of the present invention:
[0032] 1. The heavy-duty anti-corrosion material prepared by the present invention uses bisphenol epoxy resin as a matrix to give the material excellent corrosion resistance;
[0033] 2. By modifying the composite filler of nano titanium powder and graphene oxide, the compatibility with the epoxy resin matrix is improved, and the heat resistance, wear resistance and corrosion resistance of the material are greatly enhanced;
[0034] 3. The various groups in the prepared organic modifier molecules work synergistically, significantly enhancing the heat resistance, flame retardancy and corrosion resistance of the material to a certain extent, and the performance is long-lasting and stable and not easy to fall off;
[0035] Therefore, the heavy-duty anti-corrosion material prepared by the present invention has excellent wear resistance, stable and efficient heat resistance, corrosion resistance and flame retardancy, is solvent-free, has low VOC volatility, is environmentally friendly, and has important application value in harsh corrosive environments such as desulfurization towers, gas pipelines and gas tanks. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1
[0038] Preparation of organic modifiers:
[0039] S1. In a three-necked flask equipped with a stirring device, 16.3 g of tris(hydroxymethyl)aminomethane hydrochloride, 15 mL of triethylamine and 100 mL of N,N-dimethylformamide were mixed at room temperature, placed in an ice-water bath at 5°C, and stirred for 35 min. Then, 15.3 g of phosphorus oxychloride was slowly added dropwise, and the temperature was controlled not to exceed 20°C during the addition. After the addition was completed, the temperature was raised to 80°C and kept for reaction for 8 h. After the reaction was completed, the solvent was removed by filtration under reduced pressure, and the filter cake was washed 3 times with anhydrous ethanol, vacuum dried, and ground to obtain intermediate 1.
[0040] S2. In a three-necked flask equipped with a stirring device, 16.5 g of intermediate 1, 28.4 g of hexafluoroglutaryl chloride and 150 mL of N,N-dimethylformamide were mixed and stirred continuously for 5 min, and then 20.6 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 4 h. After the reaction was completed, the mixture was filtered, rotary evaporated, and the solvent was removed by reduced pressure distillation to obtain intermediate 2.
[0041] S3. In a three-necked flask equipped with a stirring device, 40.4 g of intermediate 2, 25.6 g of 4,4'-diaminodiphenyl sulfone and 200 mL of N,N-dimethylformamide were mixed and stirred evenly, and then 20.6 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 3.
[0042] S4. In a three-necked flask equipped with a stirring device, 18.3 g of p-phenylene diisocyanate, 61.7 g of intermediate 3 and 200 mL of N,N-dimethylformamide were mixed, 0.2 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, the mixture was washed twice with toluene, and the mixture was dried in vacuo to obtain an organic modifier.
[0043] Embodiment 2
[0044] Preparation of organic modifiers:
[0045] S1. In a three-necked flask equipped with a stirring device, 32.6 g of tris(hydroxymethyl)aminomethane hydrochloride, 30 mL of triethylamine and 200 mL of N,N-dimethylformamide were mixed at room temperature, placed in an ice-water bath at 5°C, and stirred for 35 min. Then, 30.6 g of phosphorus oxychloride was slowly added dropwise, and the temperature was controlled not to exceed 20°C during the addition. After the addition was completed, the temperature was raised to 80°C and kept for reaction for 8 h. After the reaction was completed, the solvent was removed by filtration under reduced pressure, and the filter cake was washed 3 times with anhydrous ethanol, vacuum dried, and ground to obtain intermediate 1.
[0046] S2. In a three-necked flask equipped with a stirring device, 33 g of intermediate 1, 56.8 g of hexafluoroglutaryl chloride and 300 mL of N,N-dimethylformamide were mixed and stirred continuously for 5 min, and then 41.2 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 4 h. After the reaction was completed, the mixture was filtered, rotary evaporated, and the solvent was removed by reduced pressure distillation to obtain intermediate 2.
[0047] S3. In a three-necked flask equipped with a stirring device, 80.8 g of intermediate 2, 51.2 g of 4,4'-diaminodiphenyl sulfone and 400 mL of N,N-dimethylformamide were mixed and stirred evenly, and then 41.2 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 3.
[0048] S4. In a three-necked flask equipped with a stirring device, 36.6 g of p-phenylene diisocyanate, 123.4 g of intermediate 3 and 400 mL of N,N-dimethylformamide were mixed, 0.4 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, the mixture was washed twice with toluene, and the mixture was dried in vacuo to obtain an organic modifier.
[0049] Embodiment 3
[0050] Preparation of inorganic fillers:
[0051] Add 1g of nano-titanium powder, 1g of graphene oxide and 100mL of ethanol aqueous solution into a flask, mix them, place them in a magnetic stirrer and stir them for 30min, then ultrasonically treat them for 30min to evenly disperse the nano-titanium powder and graphene oxide, add 4.3g of silane coupling agent KH-550, control the reaction temperature to 60°C, react for 6h, stir continuously during the reaction, and after the reaction is completed, perform reduced pressure distillation, wash, and freeze-dry to obtain an inorganic filler.
[0052] Embodiment 4
[0053] Preparation of inorganic fillers:
[0054] 2 g of nano titanium powder, 2 g of graphene oxide and 200 mL of ethanol aqueous solution were added to a flask and mixed. The mixture was placed in a magnetic stirrer and magnetically stirred for 60 min. The mixture was then ultrasonically treated for 60 min to uniformly disperse the nano titanium powder and graphene oxide. 8.6 g of silane coupling agent KH-550 was added. The reaction temperature was controlled at 60 ° C. The reaction was carried out for 6 h. Stirring was continued during the reaction. After the reaction was completed, the mixture was distilled under reduced pressure, washed and freeze-dried to obtain an inorganic filler.
[0055] Embodiment 5
[0056] 80 g of bisphenol A epoxy resin and 10 g of n-butyl glycidyl ether were added to a blender and stirred for 15 min, and then 1 g of a leveling agent (BYK-358N), 5 g of the organic modifier prepared in Example 1 and 1 g of a defoaming agent (BYK-024) were added in sequence and stirred for 15 min, and then 24 g of the inorganic filler prepared in Example 3 was added and stirred for 15 min, and finally 15 g of triethylamine was mixed and stirred to obtain a solvent-free special heavy-duty anticorrosive material.
[0057] Embodiment 6
[0058] 90 g of bisphenol A epoxy resin and 15 g of allyl glycidyl ether were added to a blender and stirred for 30 min, and then 1.5 g of a leveling agent (BYK-358N), 10 g of the organic modifier prepared in Example 2 and 1.5 g of a defoaming agent (BYK-024) were added in sequence and stirred for 30 min, and then 30 g of the inorganic filler prepared in Example 4 was added and stirred for 30 min, and finally 20 g of triethanolamine was mixed and stirred to obtain a solvent-free special heavy-duty anticorrosive material.
[0059] Embodiment 7
[0060] 100 g of bisphenol A epoxy resin and 20 g of phenyl glycidyl ether were added to a blender and stirred for 30 min, and then 2 g of a leveling agent (BYK-358N), 15 g of an organic modifier prepared in Example 2 and 2 g of a defoamer (BYK-024) were added in sequence and stirred for 30 min, and then 36 g of an inorganic filler prepared in Example 4 was added and stirred for 30 min, and finally 25 g of o-hydroxybenzyl dimethylamine was mixed and stirred to obtain a solvent-free special heavy-duty anticorrosive material.
[0061] Comparative Example 1
[0062] The organic modifier in Example 7 was replaced by a commercially available phosphorus-based flame retardant of equal quality, and the remaining steps were the same as those in Example 7 to obtain the material.
[0063] Comparative Example 2
[0064] Use a commercially available heavy-duty corrosion-resistant epoxy paint.
[0065] The following performance tests were performed on Examples 5, 6 and 7 and Comparative Examples 1 and 2 according to different test standards:
[0066] Adopt the national standard GB / T 9286-2021 "Scratch test method for paints and varnishes" to measure adhesion;
[0067] The non-volatile matter content was measured using the national standard GB / T 1725-2007 "Determination of non-volatile matter content of paints, varnishes and plastics";
[0068] The water resistance is measured using the national standard GB / T 1733-1993 "Determination of water resistance of paint films";
[0069] The national standard GB / T 1763 "Determination of chemical resistance of paint film" is used to determine the acid and alkali resistance;
[0070] The wear resistance is measured using the national standard GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method";
[0071] The national standard GB 12441-2005 "Surface fire retardant coating" was used to measure the mass loss of the sample before and after 180 days;
[0072] The sample was sprayed on a square steel plate with a side length of 10 cm, placed in an oven at 300°C, taken out after 7 days, and the surface condition of the sample was observed;
[0073] The measured results are shown in the following table:
[0074]
[0075]
[0076] It can be seen from the above table that the heavy-duty anti-corrosion material prepared in the embodiment of the present invention has better heat resistance and flame retardancy than the control example, and has excellent wear resistance and corrosion resistance, less VOC volatility, is environmentally friendly, and has long-term stable performance. It has important application value in harsh corrosive environments such as desulfurization towers, gas pipelines and gas tanks.
[0077] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0078] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a solvent-free special heavy-duty anti-corrosion material, characterized in that: The following steps are involved: After adding bisphenol A epoxy resin and diluent into a mixer and stirring, then add leveling agent, organic modifier and defoamer in sequence and stir, then add inorganic filler and stir, finally mix with curing agent and stir evenly to obtain solvent-free special heavy-duty anti-corrosion material.
2. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 1, characterized in that: The organic modifier is prepared by the following steps: S1. Tris(hydroxymethyl)aminomethane hydrochloride, triethylamine and N,N-dimethylformamide were mixed at room temperature, placed in an ice-water bath at 5°C, and stirred for 35 minutes. Phosphorus oxychloride was added dropwise, and the temperature was controlled not to exceed 20°C during the addition. After the addition was completed, the mixture was reacted at 80°C for 8 hours. After the reaction was completed, the mixture was filtered under reduced pressure, washed, dried in vacuo, and ground to obtain intermediate 1. S2, the intermediate 1, hexafluoroglutaryl chloride and N,N-dimethylformamide were mixed and stirred continuously for 5 minutes, and then dicyclohexylcarbodiimide was added, and the mixture was kept in a water bath at 55°C for 4 hours. After the reaction was completed, the mixture was filtered, rotary evaporated, and distilled under reduced pressure to obtain the intermediate 2; S3, after mixing and stirring the intermediate 2, 4,4'-diaminodiphenyl sulfone and N,N-dimethylformamide, dicyclohexylcarbodiimide was added, and the mixture was reacted at 55°C for 8 hours. After the reaction was completed, the mixture was filtered, rotary evaporated, purified by column chromatography, and rotary evaporated to obtain the intermediate 3; S4. Mix p-phenylene diisocyanate, intermediate 3 and N,N-dimethylformamide, add tributyltin and stir evenly, gradually increase the temperature to 70°C, keep the reaction for 6 hours, stir continuously during the reaction, and after the reaction is completed, perform vacuum distillation, wash, and vacuum dry to obtain an organic modifier.
3. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 2, characterized in that: In step S1, the ratio of tris(hydroxymethyl)aminomethane hydrochloride, triethylamine, N,N-dimethylformamide, and phosphorus oxychloride is 16.3 g:15 mL:100 mL:15.3 g.
4. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, hexafluoroglutaryl chloride, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 16.5 g: 28.4 g: 150 mL: 20.6 g.
5. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, 4,4'-diaminodiphenyl sulfone, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 40.4 g:25.6 g:200 mL:20.6 g.
6. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 2, characterized in that: In step S4, the ratio of the amount of p-phenylene diisocyanate, intermediate 3, N,N-dimethylformamide and tributyltin is 18.3 g:61.7 g:200 mL:0.2 g.
7. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of bisphenol A epoxy resin, 10-20 parts of diluent, 1-2 parts of leveling agent, 5-15 parts of organic modifier, 1-2 parts of defoamer, 24-36 parts of inorganic filler, and 15-25 parts of curing agent.
8. The method for preparing a solvent-free special heavy-duty anticorrosive material according to claim 1, characterized in that: The inorganic filler is prepared by the following steps: Nano-titanium powder, graphene oxide and ethanol aqueous solution were added to a flask and mixed, and then placed in a magnetic stirrer for magnetic stirring and ultrasonic treatment to evenly disperse the nano-titanium powder and graphene oxide. Silane coupling agent KH-550 was added, and the reaction temperature was controlled at 60°C. The reaction was carried out for 6 hours with continuous stirring during the reaction. After the reaction was completed, the inorganic filler was obtained by vacuum distillation, washing and freeze-drying.
9. Application of the heavy-duty anti-corrosion material obtained by the preparation method according to claim 1 in the fields of desulfurization towers, gas pipelines, and gas tanks.
Citation Information
Patent Citations
Long-acting acid-base resistant solvent-free anticorrosive paint as well as preparation method and application thereof
CN103666201A
Method for preparing phosphorous-nitrogen synergistic wood fire retardant
CN105538451A
Composite reinforced anticorrosive coating composition containing graphene and nano titanium
CN112592616A
Method for producing diphenyl sulfone diisocyanate
JP2007254292A
Cited By
Heat-resistant organic silicon pressure-sensitive adhesive and preparation method thereof
CN120041145A